UV‐laser marking of a TiO2‐containing ABS material. Issue 9 (26th October 2017) - Clemente, M.J.; Lavieja, C.; Peña, J.I.; Oriol, L.
Abstract : Marking of titanium dioxide‐containing ABS polymeric samples was accomplished using a UV laser that induces a white to grey color change with only a minor alteration of the plastic material. The characterization of this marking process has been conducted by different techniques to determine the quality of the UV‐laser marking and to gain an insight into how the plastic material is affected by laser irradiation. Surface characterization was performed and tests were conducted to evaluate the potential applications of this UV‐marking process. POLYM. ENG. SCI., 58:1604–1609, 2018. © 2017 Society of Plastics Engineers